Mothers and fathers with intellectual and developmental disabilities who use US disability services: prevalence and living arrangements. Issue 3 (23rd December 2021) - Stancliffe, R. J.; Pettingell, S. L.; Tichá, R.; Houseworth, J.
Abstract: Background: Little information is available on the prevalence of mothers and fathers with intellectual and developmental disabilities among US disability‐service users. Child removal is a key issue for these parents. Methods: We analysed 2018–19 National Core Indicators data from 35 states on US adults with intellectual and developmental disabilities being a parent. For parents of a child under 18, we examined whether the child lived with them. Results: Prevalence of parenthood was 3.7% (6.0% women, 2.1% men). Among parents of a child under 18, 44.0% had their child living with them. Being a mother, being married and living with family were positively associated with child co‐residence. Parents with co‐resident children mainly lived in their own home (59.7%) or their family's home (32.3%). Conclusions: Our prevalence estimate suggests a national total of 33 794 US parents who use intellectual and developmental disabilities services. For parents living with their child, a critical task for disability services is to enable parents and children to live in a family setting.